Rancang Bangun Heating Mantle Aquadest Dengan Pendekatan Ergonomi Berbasis Arduino - Hikmah Maya Sari; Kusnadi Kusnadi; Muhammad Akbar Hariyono; Muhammad Zaini; Galih Persadha (Health Media, 2023)
A laboratory support facility called "Heating Mantle" for aquadest distillation is urgently needed in the laboratory to be used as a cleaning tool as well as a mixture of chemicals in the laboratory. This research aims to make it easier to obtain aquadest water and reduce the high price of distillation equipment on the market, so researchers make a Heating Mantle tool. The method used in this research is Research and Development (RnD), by developing from previous research. The development carried out is in the control of the heating system using an electric stove and is equipped with a timer feature to make it easier for users to regulate and monitor distillation process, as well as with the DS18B20 sensor used to measure the water temperature in the chamber whose results will be displayed by OLED. The results of aquadest measurements with PDAM tap water samples have a pH level of 8.2 and Aquadest has a pH level of 7.9. The product test results can be concluded that when the product is tested on PDAM water, the result is that the water can be pure aquadest water. In the validation of the tool from material experts, the results were 93.3% and media experts obtained 86.6%. When seen in the feasibility category table, the result is "Very Eligible".